INTERNATIONAL LAW STANDARDS ON THE RIGHT TO COMPENSATION FOR WRONGFUL CONVICTION (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2021)
Once the criminal procedure has been initiated, the mechanism of criminal-law protection of social values is set in motion, imposing immediate restrictions оn the fundamental human rights of the accused. To ensure that the judgment rendered in criminal proceedings is fully legitimate, the legislator has to ensure that the defendant has the opportunity to articulate his/her position оn the matter at issue. The legislator has to balance the public interest of the state to punish the criminal offender аnd the fundamental human rights аnd freedoms of individuals who are subjected to the criminal-law repression. To this effect, it is necessaryto create an optimal institutional setting which would embody these opposing goals. The defendant’s fundamental human rights and freedoms may be restricted only if the judgment imposing such restrictions has been the result of а confrontation of arguments between the prosecutor and the defendant in proceedings instituted before an independent criminal court which has fully observed the principles of legality, impartial justice and fairness. Thisis the essence of the right to а fair trial, which is contained in the international human rights’ protection documents and the supreme legal acts of the states based оn the rule of law. The right to а fair trial comprises the right of the injured party (the “victim” of unfair criminal proceedings) to seek compensation from the state for wrongful conviction. This right is considered infringed if there has been а serious omission in the course of proceedings which is detrimental to the defendant’s interests. It encompasses the rights arising from wrongful conviction and wrongfully applied procedural repression measures. As such, thisright is envisaged in the most important international law documents in the field of human rights’ protection.